4WD mobile robot for autonomous steering using single camera based vision system. Issue 3 (5th August 2014) - Hyuc Ko, Min; Chul Kim, Kyoung; Suprem, Abhijit; Prem Mahalik, N.; Sahng Ryuh, Boem
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to demonstrate System-of-Systems (SoS) approach to design and development of unmanned robotic platform for greenhouse agricultural application. Design/methodology/approach – SoS design approach is important in developing engineering products. It was observed that while system integration considers designs in a multi-disciplinary level framework, SoS is viewed as a solution focussed approach. In this paper, the authors have demonstrated SoS approach to develop a mobile robot platform. The wheels of the platform are independently controlled by using brushless DC and stepper motors based on fieldbus type Distributed Control System scheme. Findings – The constraints for autonomous traveling were identified during the first phase followed by development of 12 distinct sub-routines during second phase of training. Optimal camera installation angle, driving speeds, steering angle per pixel were found to be valuable constraints for feed-forward parameters for real-time driving. The platform was field tested in a tomato planted greenhouse for yield and weed mapping. Research limitations/implications – The paper focusses on studying vision-based autonomous four-wheel-drive (4WD) constraints and their implementation limitations. Practical implications – The platform was field tested in a tomato planted greenhouse for yield and weed mapping. Social implications – The platform can be used for agricultural operations such as crop scouting, monitoring, spraying, and mapping in a medium to large-scale greenhouse setting. Originality/value – The research and presentation is original. Starting from its mechanical specification to wheel performance study, development of path patterns for training and global navigation algorithm for testing and validation were achieved. The platform can autonomously be driven without any manual intervention.